2019
DOI: 10.1111/dom.13693
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic goal attainment and hypoglycaemia outcomes in type 2 diabetes patients initiating insulin glargine 300 units/mL or 100 units/mL: Real‐world results from the DELIVER Naïve cohort study

Abstract: Aims To compare HbA1c and hypoglycaemia in insulin‐naïve patients with type 2 diabetes (T2D) who initiated insulin glargine 300 units/mL (Gla‐300) or 100 units/mL (Gla‐100). Materials and methods This retrospective cohort study examined electronic medical records of insulin‐naïve adults with T2D who initiated Gla‐300 or Gla‐100 during March 2015 through to December 2016 with active records for ≥12 months before and ≥6 months after initiation, and ≥1 valid HbA1c value du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 18 publications
7
46
0
Order By: Relevance
“…This led to comparable mean reductions in HbA1c (−1.22% vs. –1.29%) observed 12 months after starting Gla‐300 treatment in our study and in EDITION 3 . In two recently published observational studies evaluating electronic medical records, insulin‐naïve type 2 diabetes patients in the United States were reported to reduce HbA1c levels by −1.67% and −1.52%, respectively, during 3 to 6 months follow‐up; however, both studies started from higher baseline HbA1c values of 9.7% and 9.6%, respectively …”
Section: Discussionsupporting
confidence: 74%
“…This led to comparable mean reductions in HbA1c (−1.22% vs. –1.29%) observed 12 months after starting Gla‐300 treatment in our study and in EDITION 3 . In two recently published observational studies evaluating electronic medical records, insulin‐naïve type 2 diabetes patients in the United States were reported to reduce HbA1c levels by −1.67% and −1.52%, respectively, during 3 to 6 months follow‐up; however, both studies started from higher baseline HbA1c values of 9.7% and 9.6%, respectively …”
Section: Discussionsupporting
confidence: 74%
“…Retrospective RWE corroborates a comparable glycemic control and reduced hypoglycemia with second-generation compared with firstgeneration BI analogues [42][43][44][45][46], with potential cost offsets from a reduction in healthcare utilization and hospitalizations [44]. These findings have been observed in both insulin-naïve T2DM populations [45,46] and in participants who switched from another BI analogue [42][43][44].…”
Section: Methodssupporting
confidence: 62%
“…Results for RWE studies also support the efficacy and safety of second-generation BIs in individuals with T2DM and obesity [42,43,51,52]. For example, in the DELIVER 3 [42], DELIVER Naïve [46], DELIVER Naïve D [45], DELIVER D?, [51] CONFIRM [52] and LIGHTNING [43] studies, the mean baseline BMI of patients was approximately 33-35 kg/ m 2 . Similarly, most patients in the SWITCH 2 double-blind, cross-over study with IDeg versus Gla-100 had obesity, with an mean BMI of 32.2 kg/m 2 .…”
Section: Obesitymentioning
confidence: 78%
“…6 The DELIVER Naive real-world observational study, which used electronic medical record (EMR) data, showed improved HbA1c control and suggested reduced hypoglycaemia with Gla-300 versus Gla-100 in insulin-naïve adults with T2D. 7 Two other real-world, observational studies (DELIVER D 8 and DELIVER D+ 9 ) compared Gla-300 and IDeg in patients with T2D who switched from first-generation basal insulin analogues. Both studies found that Gla-300 and IDeg resulted in comparable reductions in HbA1c and similar levels of hypoglycaemia.…”
Section: Introductionmentioning
confidence: 99%